2019
DOI: 10.1038/s41598-019-49725-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of Globodera pallida from the susceptible host Solanum tuberosum or the resistant plant Solanum sisymbriifolium

Abstract: A transcriptome analysis of G. pallida juveniles collected from S. tuberosum or S. sisymbriifolium 24 h post infestation was performed to provide insights into the parasitic process of this nematode. A total of 41 G. pallida genes were found to be significantly differentially expressed when parasitizing the two plant species. Among this set, 12 were overexpressed when G. pallida was parasitizing S. tuberosum and 29 were overexpressed when parasitizing S. sisymbriifolium. Out of the 12 genes, three code for sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
(55 reference statements)
0
16
1
1
Order By: Relevance
“…Interactions of G. pallida with its natural host Solanum tuberosum and a resistant plant Solanum sisymbriifolium was investigated previously (Kooliyottil et al, 2016(Kooliyottil et al, , 2019. A hypersensitive response (HR) was evident as early as 24 h post infestation in the root cells of S. sisymbriifolium (Kooliyottil et al, 2016).…”
Section: Abc Transporters In Plant-parasitic Nematodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactions of G. pallida with its natural host Solanum tuberosum and a resistant plant Solanum sisymbriifolium was investigated previously (Kooliyottil et al, 2016(Kooliyottil et al, , 2019. A hypersensitive response (HR) was evident as early as 24 h post infestation in the root cells of S. sisymbriifolium (Kooliyottil et al, 2016).…”
Section: Abc Transporters In Plant-parasitic Nematodesmentioning
confidence: 99%
“…A hypersensitive response (HR) was evident as early as 24 h post infestation in the root cells of S. sisymbriifolium (Kooliyottil et al, 2016). Transcriptome analysis of G. pallida juveniles isolated from resistant S. sisymbriifolium or the susceptible host, potato, 24 h post infestation showed expression of several genes related to the xenobiotic metabolism (Kooliyottil et al, 2019). G. pallida isolated from S. tuberosum and S. sisymbriifolium showed that there were 18 G. pallida ABC transporters (GPLIN_000375400, GPLIN_001624000, GPLIN_000079800, GPLIN_000593000, GPLIN_000607700, GPLIN_000662100, GPLIN_000762600, GPLIN_000764700, GPLIN_000165600, GPLIN_001513300, GPLIN_000934100, GPLIN_001038000, GPLIN_001558100, GPLIN_001072100, GPLIN_000043700, GPLIN_001213800, GPLIN_001600700, and GPLIN_000055000) expressed during plant infection (Kooliyottil et al, 2019).…”
Section: Abc Transporters In Plant-parasitic Nematodesmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-seq profiling has been used to decipher potato responses to various abiotic [ 15 , 16 ] and biotic stresses [ 17 , 18 ] where large sets of genes and pathways associated with either biotic and abiotic stress were revealed. To date, most research has focused on potato gene expression in response to potato cyst nematodes [ 19 , 20 , 21 ] while potato responses to RKN infestation remain poorly understood. Here, we set out to evaluate the molecular basis of Potato-RKN compatible interaction, we employed RNA-Seq to analyze differential gene expression patterns in S. tuberosum cv.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq profiling has been used to decipher potato responses to various 86 abiotic (Zuluaga et al, 2015, Gálvez et al, 2016 and biotic stresses (Kwenda et al, 2016, Yang 87 et al, 2018 where large sets of genes and pathways associated with either biotic and abiotic 88 stress were revealed. To date most research has focused on potato gene expression in response 89 to potato cyst nematodes (Jolivet et al, 2007, Walter et al, 2018, Kooliyottil et al, 2019 while 90 potato responses to RKN infection remain poorly understood. Here, we set out to evaluate the 91 responses of potato cultivars to root-knot nematode infection.…”
Section: Introduction 41mentioning
confidence: 99%